DEGRADASI LINGKUNGAN DI KAWASAN PENYANGGA SUAKA MARGASATWA BUKIT RIMBANG BUKIT BALING PROPINSI RIAU - Indra Suandy; Aras Mulyadi; Setyo S. Moersidik; Emirhadi Suganda (Jurnal Ilmu Lingkungan, 2014)
The environmental conditions of Wildlife Sanctuary buffer zones Bukit Rimbang BukitBaling (SM BRBB) alleged to have been degraded by a variety of community activities.This research aims to determine the condition and degradation of SM BRBB bufferzone. The survey was conducted in the buffer zone of SM BRBB, especially located inthe district of Kuantan Singingi, Riau Province. The forest area in the buffer zone of SMBRBB is located in hilly areas, composed by primary forest and secondary forest. In2004 the forest buffer zones is amounted to 14539.98 ha, and shrinkage to 82.25% in2008. The major threats of SM BRBB buffer zone comes from illegal logging,Industrial Plantation Forest (IPF), farms and settlements. In the period of 2004-2008,there has been a vast increase of IPF amounted to 195.76% of the initial area amountedto 8198.39 ha, plantation area of 159.74% of the initial area 2300.89 ha, and theaddition of extensive settlement of 222.56% of the initial area of 29.97 ha.